2014 IEEE International Conference on Automation Science and Engineering (CASE) 2014
DOI: 10.1109/coase.2014.6899445
|View full text |Cite
|
Sign up to set email alerts
|

The experiments of wearable robot for carrying heavy-weight objects of shipbuilding works

Abstract: The purpose of this research is to assess an applicability of wearable robot for the shipbuilding works. We developed two types of wearable robot that can be separated by actuation mechanism; one is directly actuated by electric motors and another is actuated by electro-hydraulic actuators. The lifting capacity of both of the robot is currently about 30kg. We performed field tests in 7 kinds of workplaces for handling and installing heavy-weight objects such as pipeline outfitting components, small metal compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…It should be noted that earlier work has shown that maintaining balance when using a WB-PEXO can be demanding without an active control of balance [27], [30]. The XO prototype examined here did not have such a control layer at the time of testing.…”
Section: Difficulty Controlling a Wb-pexo?mentioning
confidence: 91%
See 1 more Smart Citation
“…It should be noted that earlier work has shown that maintaining balance when using a WB-PEXO can be demanding without an active control of balance [27], [30]. The XO prototype examined here did not have such a control layer at the time of testing.…”
Section: Difficulty Controlling a Wb-pexo?mentioning
confidence: 91%
“…Several other WB-PEXOs have been developed. For example, in 2010 Panasonic Activelink presented a WB-PEXO designed for heavy-duty jobs [29], and the Daewoo WB-PEXO prototype was described in 2014 had a lifting capacity of 30 kg during tasks relevant to shipbuilding [30].…”
Section: Introductionmentioning
confidence: 99%
“…Further, it is discussed that such system can be utilized in any field where the step voltage hazard is common and frequent. Chu et al [15] performed experimental studies to find the scope of wearable robots in shipbuilding environment for the workers. The main motivation of such study is to reduce the work load and help the workers to lift heavy weight objects from one place to other.…”
Section: Related Workmentioning
confidence: 99%
“…With the recent rapid growth of the wearable robot market, a variety of wearable robots are being developed and utilized for various purposes, such as for the rehabilitation of patients suffering from neurological or musculoskeletal disorders or assisting elderly people suffering from weak muscle strength [ 1 , 2 , 3 , 4 ]. Wearable robots also assist workers to prevent musculoskeletal disorders and improve productivity at industrial sites [ 5 , 6 , 7 , 8 , 9 ]. The technology that enables robots to interact with humans so that they can make their own decisions is called human–robot interaction (HRI).…”
Section: Introductionmentioning
confidence: 99%